Risk prediction of drug-drug interaction potential of phenytoin and miconazole topical formulations. (1st July 2021) - Li, Wei; Wang, Zhen; Wang, Xiaoyu; Cao, Xiaowei; Bi, Caili; Jiang, Lili; Cui, Shuna; Liu, Yong
Abstract: The drug-drug interaction (DDI) risk of phenytoin with several topical formulations of miconazole is still unclear. The present investigation conducted in vitro - in vivo extrapolation to predict the potential risks. Our data indicated that miconazole potently inhibited phenytoin hydroxylation in both pooled human liver microsomes (HLMs) and recombinant cytochrome P450 2C9 (CYP2C9) with the K i values of 125 ± 7 nM and 30 ± 2 nM, respectively. Quantitative prediction of DDI risk suggests that, beside intravenous administration or swallowed tablet, combination of phenytoin and miconazole high dose oral gel or buccal tablet may also result in a clinically significant increase of phenytoin AUC (>53%) by the inhibition of miconazole against phenytoin hydroxylation, consequently a higher frequency of adverse events, while the coadministration of miconazole vaginal formulation and phenytoin will be safe. Graphical abstract: Image 1 Highlights: Miconazole was a potent inhibitor of phenytoin hydroxylation catalyzed by CYP2C9. Miconazole high dose oral gel or buccal tablet may trigger off phenytoin toxicity. Miconazole vaginal gel or low dose oral gel cannot lead to phenytoin toxicity.